1998
DOI: 10.1016/s0022-5347(01)63835-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Intravesical Bacillus Calmette-Guerin Therapy for Superficial Bladder Cancer by Immunological Urinary Measurements: Statistically Weighted Syndromes Analysis

Abstract: We have selected a set of urinary variables that could be considered as a perspective combination of indicators (syndromes) of outcome of pre-operation BCG therapy of patients with superficial bladder cancer. A larger patient database will provide testing and evaluation of the biological and clinical significance of selected features. The computational syndrome-disease approach should be applicable for the solution of decision-making problems for management of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
8

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 0 publications
0
22
0
8
Order By: Relevance
“…PAM is a modification of the nearest-centroid method and was applied as previously described (25). SWS is a supervised, combinatorial pattern recognition method based on a statistical voting procedure that uses selected subsets of predictors that act alone or in combination (26,27). Briefly, the methodology is based on several steps: (a) optimal recoding of the given covariates to obtain discrete-valued variables; (b) selection of the most informative and statistically robust of these discrete-valued variables and their combinations (termed syndromes) that best characterize the classes of interest; (c) tallying the statistically weighted ''votes'' of these syndromes to compute the value of the outcome prediction function (by leave-one-out cross-validation).…”
Section: Methodsmentioning
confidence: 99%
“…PAM is a modification of the nearest-centroid method and was applied as previously described (25). SWS is a supervised, combinatorial pattern recognition method based on a statistical voting procedure that uses selected subsets of predictors that act alone or in combination (26,27). Briefly, the methodology is based on several steps: (a) optimal recoding of the given covariates to obtain discrete-valued variables; (b) selection of the most informative and statistically robust of these discrete-valued variables and their combinations (termed syndromes) that best characterize the classes of interest; (c) tallying the statistically weighted ''votes'' of these syndromes to compute the value of the outcome prediction function (by leave-one-out cross-validation).…”
Section: Methodsmentioning
confidence: 99%
“…cancer therapy ͉ immunotherapy ͉ tumor homing A lthough reports of using bacteria to treat tumors in humans date as far back as to 1893 (1), thus far, microbial-based approaches to cancer immunotherapy are limited to use of bacillus Calmette-Guérin (BCG) for superficial bladder carcinomas (2,3). It has been reported that bacteria administered by i.v.…”
mentioning
confidence: 99%
“…The use of live bacteria for the treatment of cancer has thus far been limited to bacillus Calmette-Guérin (BCG) for the treatment of superficial bladder carcinomas and is administered by urethral catheterization [7]. Although the mechanism of action is unknown, it is thought that BCG works by induction of anti-tumor immunity attributable to the inflammatory response and production of cytokines following BCG administration [8].…”
mentioning
confidence: 99%